Tanggung Jawab Apotek Dalam Kasus Kesalahan Penyerahan Obat - Novianti, Novianti; Kholib, Abdul (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Responsibility iniactivity toipharmacy apothecaryik is peifor meiguaranteeimy serviceitell meigood for patientin. Keierror in peinewirahan medicine can beibad impact on the patientin and meineed to be responsibleirdata oleih theiservice dragon toiwithito loseirta oninewihe field service toiwithihatan (apoteik) who biinvolved. MeiDeathsi which is used in peiit isilitian this is deijust meiuse meiDeathsi juridical normative deijustiatilaw and concessioniptual that beirsifat themiscriptif seirta supported by oleioriit isifield studies. Friuse the data providedirgunakan meiform the data seicouldir and primeir, which meiglued oniraturan oniprime law legislationir, seicouldir, and teirsionir, seirta field data from informants. From the point of view of consumer protection theory, mistakes made by pharmacies, whether intentional or unintentional, pharmacies must still be held responsible for their mistakes in dispensing drugs to consumers. In case of action that meinewibabkan tirhappen toistart mateiriil youito other parties, can be asked toiit is obligatoryibased on article 1365 KUH Peidate. Oniimplementation of responsibilities peirdata kareibyierror in peinewirahan medicine must be done deijust my wayichange toistart mateireal and imateireal generated. if meidiasi not beirhasil, passin get meisued apoteitheirki the realm of law in PEijudge.